Early Endocarditis and Delayed Left Ventricular Pseudoaneurysm Complicating a Transapical Transcatheter Mitral Valve-in-Valve Implantation: Percutaneous Closure Under Local Anesthesia and Echocardiographic Guidance. (October 2016) - Salaun, Erwan; Aldebert, Philippe; Jaussaud, Nicolas; Spychaj, Jean-Charles; Maysou, Laurie Anne; Collart, Frederic; Avierinos, Jean-François; Casalta, Jean-Paul; Cuisset, Thomas; Hubert, Sandrine; Lambert, Marc; Raoult, Didier; et al.
Abstract : Supplemental Digital Content is available in the text.